STRATEGI PENGENTASAN KEMISKINAN (Perspektif Sosial Ekonomi Kerakyatan) - Abd. Rasyid Masri (Jurnal Berita Sosial, 2018)
Poverty Reduction Strategy (Perspective of Socio-Economic Communities) examines the factors causing poverty, and poverty alleviation strategies. This research method uses a kind of qualitative approach that is done intensive, in-depth, detailed and comprehensive with the stages of doing exploration where the target of research by using phenomenology method, then formulate theories that lead researchers to seek more in the issues studied, while the technique data collection is natural setting with the sense that expected what kind of events experienced by individuals and not influenced by the presence of researchers in the family. Besides that, descriptive data were collected, in-depth interviews, documentation study observation and Miles and Huberman model data analysis, data reduction, data presentation, and conclusion.The results showed that the causes of poverty are institutional and policy factors, limiting factors of natural resources, factors in the community, the lack of opportunity plus the mental attitude that resigned to the situation, lazy beker je and trying and lain.Sedangkan government efforts in alleviating poverty that is training and special education, mental guidance towards independence and the kretivitas of the poor, and others. In poverty alleviation besides the perspective of populist economy, there is also a socio-cultural perspective and even a religious perspective can also be effective in encouraging and motivating people to get out of the crush of poverty.Keywords: